The The Influence of Digital Marketing and Product Quality on Product Purchasing Decisions in Jepara Furniture MSMEs (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of digital marketing and product quality on purchasing decisions in furniture MSMEs in Jepara Regency as the object of research. The main problem in this study is the increasing business competition that requires MSMEs to optimize digital marketing strategies without ignoring product quality in influencing consumer purchasing decisions. The research method used is a quantitative approach with a survey method, where data is collected by distributing questionnaires to selected furniture MSME consumers using a purposive sampling technique. Data analysis was carried out by testing validity, reliability, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that digital marketing has a positive and significant effect on purchasing decisions. Product quality also has a positive and significant effect on purchasing decisions and is the most dominant variable. Simultaneously, digital marketing and product quality have a significant effect on purchasing decisions with a coefficient of determination of 0.784. These findings conclude that the integration of digital marketing strategies and continuous improvement of product quality are important factors in improving purchasing decisions and the competitiveness of furniture MSMEs in the digital era.